The incidence and burden of time loss injury in Australian men`s sub-elite football (soccer): A single season prospective cohort study - Whalan, M.; Lovell, R.; McCunn, R.; Sampson, J. A. (Journal of Science and Medicine in Sport, 2019)
Objectives: This study aimed to conduct the first injury surveillance study in sub-elite football in Australia, using methods from the international football consensus statement. Design: Descriptive epidemiological study. Methods: 1049 sub-elite football players were recruited during the 2016 season. Injury and exposure data was collected by trained Primary Data Collectors (PDCs) who attended every training session and match. Results: There were 1041 time loss injuries recorded during 52,127 h of exposure resulting in an injury incidence rate of 20 injuries/1000 h (95% Confidence Interval [CI]: 15.9-23.3). The injury burden (days lost to injury relative to exposure) was 228 days lost/1000 h. Muscle and ligament injuries were the most prevalent (41% and 26%) and incurred the highest injury burden (83 and 80 days lost/1000 h, respectively). The most common injuries were observed at the thigh (22%) and ankle (17%), with hamstring (13%) the highest reported muscle injury. The profile of injury severity was: mild — 35%; minor — 29%; moderate — 28% and severe — 8%. Recurrent injuries accounted for 20% of all injuries. Conclusions: By addressing issues identified with injury recording in sub-elite football, this study found that the injury incidence was twice that observed in previous research in elite and sub-elite football cohorts. Injury burden was also twice that of the elite setting, with similar injuries associated with the highest burden. The results highlight the need for investment into medical provision, facilities, coach education and injury mitigation programmes to reduce healthcare costs to sub-elite players in Australia. ABSTRACT FROM AUTHOR